Spremljanje kondicijskega stanja betonskih težnostnih pregrad - Klun, Mateja (Acta hydrotechnica, 2021)
The ageing of dams is one of the major challenges in specifically Slovenian and generally global dam engineering. Dams are exposed to environmental (climate) changes, as well as time-dependent effects, such as changes in the operating schedules of dams intended primarily for hydroelectric production. These changes can accelerate dams’ ageing and lead to a decrease in their structural and operational safety. Dams are an important part of the infrastructure, as they bring about numerous benefits and at the same time they are also sources of risk. For example, in the event of partial or total failure they pose significant risk to downstream areas. Aging of dams, preserving their functionality, and maintaining their structural health are currently the main challenges of dam engineering. The mean age of Slovenian dams is already over 40 years, although Slovenia is not unique in this situation. In this paper there is presented a novel methodology to monitor structural health of concrete dams, with the use of noncontact and contact measurements through observation of structural vibrations. We present the in-situ experiment on the Brežice dam that began during the dam’s construction and continued into the first year of its operation.
Keywords: betonske pregrade; concrete dams; hidrotehnika; measurements; meritve; spremljanje kondicijskega stanja; spremljanje vibracij; structural health monitoring; vibration monitoring